mTOR Co-Targeting in Cetuximab Resistance in Head and Neck Cancers Harboring PIK3CA and RAS Mutations - Wang, Zhiyong (Oxford University Press, 2014)
BACKGROUND: Cetuximab, a monoclonal blocking antibody against the epidermal growth factor receptor EGFR, has been approved for the treatment of squamous cell carcinomas of the head and neck (HNSCC). However, only few patients display long-term responses, prompting the search for cetuximab resistance mechanisms and new therapeutic options enhancing cetuximab effectiveness. METHODS: Cetuximab-sensitive HNSCC cells were retro-engineered to express PIK3CA and RAS oncogenes. These cells and HNSCC cells harboring endogenous PIK3CA and RAS oncogenes were xenografted into mice (n = 10 per group) and studied for their biochemical, antitumor, antiangiogenic, and antilymphangiogenic responses to cetuximab and mTOR targeting agents. All P values are two-sided. RESULTS: Cetuximab treatment of PIK3CA- and RAS-expressing HNSCC xenografts promoted an initial antitumor response, but all tumors relapsed within few weeks. In these tumors, cetuximab did not decrease the activity of mTOR, a downstream signaling target of EGFR, PIK3CA, and RAS. The combined administration of cetuximab and mTOR inhibitors exerted a remarkably increased antitumor activity, particularly in HNSCC cells that are resistant to cetuximab as a single agent. Indeed, cotargeting mTOR together with cetuximab caused a rapid tumor collapse of both PIK3CA- and RAS-expressing HNSCC xenografts (P < .001), concomitant with reduced proliferation (P < .001) and lymphangiogenesis (P < .001). CONCLUSION: The presence of PIK3CA and RAS mutations and other alterations affecting the mTOR pathway activity in HNSCC could be exploited to predict the potential resistance to cetuximab, and to select the patients that may benefit the most from the concomitant administration of cetuximab and PI3K and/or mTOR inhibitors as a precision molecular therapeutic option for HNSCC patients.